Myofascial and balance tests after anterior cruciate ligament reconstruction in adolescent patients - Szlachta Grzegorz; Dębski Przemysław; Kublin Kamil; Woźniak Piotr; Marek Maciej (Sciendo, 2023)
Study aim: The functional assessment of patients after anterior cruciate ligament reconstruction (ACLR) is one of the key points in deciding whether one can safely return to physical activity. The aim of this study is to investigate the usefulness of the NEURAC® tests and single leg balance test (SLBT) in the functional evaluation of adolescent patients after ACLR to detect differences between the operated and non-operated extremity.